Glass Half Full: Civic Space and Contestation in Bangladesh, Sri Lanka and Nepal - Surie, Mandakini D.; Saluja, Sumaya; Nixon, Nicola (The Asia Foundation, 2023)
The past decade has witnessed a surge of interest in and concern over the global trend toward democratic regression. In South Asia, regulato ry and institutional frameworks have become increasingly restrictive, curbing the ability of citizens and civil society organizations to occ upy and use civic spaces to organize, express themselves, and particip ate in decisions that affect the lives of people whose interests they serve. Of course, this is only one half of the story. The other half i s how citizens, collectives, and organizations adapt by carving out sp aces where they can maintain—or even expand—the boundaries of their en gagement in local and national civic spaces. In this paper, we examine how civic spaces are evolving in three South Asian countries—Banglade sh, Sri Lanka, and Nepal—drawing on the experiences and perspectives o f civil society representatives. The paper concludes with recommendati ons for donors and development practitioners on how they can make rele vant investments that will strengthen civic spaces and support democra tic resilience in the region.